2023
DOI: 10.1007/s00167-023-07374-3
|View full text |Cite
|
Sign up to set email alerts
|

Hospital variation in revision rates after primary knee arthroplasty was not explained by patient selection: baseline data from 1452 patients in the Danish prospective multicenter cohort study, SPARK

Abstract: Purpose Revision rates following primary knee arthroplasty vary by country, region and hospital. The SPARK study was initiated to compare primary surgery across three Danish regions with consistently different revision rates. The present study investigated whether the variations were associated with differences in the primary patient selection. Methods A prospective observational cohort study included patients scheduled Sep 2016 Dec 2017 for primary knee a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Kurtz et al found that in 2006, the percentage of patients younger than 65 years who underwent primary TKA increased to 40 % of the total number of TKAs performed [9]. Despite the large number of factors that determine the effectiveness of arthroplasty, a multicentre study noted that differences in patient selection did not correspond to the frequency of revision interventions, but instead were due to subjective factors influencing treatment [10]. This emphasises the need for a differentiated approach to the choice of surgical treatment in patients with knee osteoarthritis.…”
Section: Introductionmentioning
confidence: 99%
“…Kurtz et al found that in 2006, the percentage of patients younger than 65 years who underwent primary TKA increased to 40 % of the total number of TKAs performed [9]. Despite the large number of factors that determine the effectiveness of arthroplasty, a multicentre study noted that differences in patient selection did not correspond to the frequency of revision interventions, but instead were due to subjective factors influencing treatment [10]. This emphasises the need for a differentiated approach to the choice of surgical treatment in patients with knee osteoarthritis.…”
Section: Introductionmentioning
confidence: 99%